Predicted warming intensifies the negative effects of nutrient increase on tropical seagrass: A physiological and fatty acid approach. (September 2022) - Beca-Carretero, Pedro; Azcárate-García, Tomás; Teichberg, Mirta; Patra, Priyanka; Feroze, Farhan; González, Maria J.; Medina, Isabel; Winters, Gidon
Highlights: Predicted warming will favour Halophila stipulacea photosynthetic and growth responses. Nutrients reduced Fv/Fm and seagrass production while favouring algae proliferation. Warming enhanced the detrimental effects of eutrophication on seagrasses. Fatty acids unsaturation and elongation indexes can be used as eco-physiological indicators. Rises in temperature and nutrients reduced the accumulation of omega-3 fatty acids. Abstract: The Gulf of Aqaba (GoA; northern Red Sea) supports extensive seagrass meadows, dominated by the small tropical seagrass species, Halophila stipulacea . Due to its semi-closed structure, in the GoA, regional nutrient loading and global warming are considered the biggest threats to local seagrass meadows, and their combination can potentially amplify their negative impacts. Using a seagrass-dedicated mesocosm, we exposed two seagrass populations with different local "nutrient history" to control (27 °C) and simulated warming (31 °C), with and without nutrients (20 µM DIN). Following four weeks of these treatments ("stress phase"), all plants were returned to control conditions ("recovery phase") for another three weeks. Results showed that exposure to only thermal stress favoured growth, compared to exposure to only nutrient increase that reduced Fv /Fm and growth but favoured algae proliferation. Exposure to the combined thermal and nutrient stress, negatively affected seagrass performance resulting in high mortality observed after four weeks of combined exposure. The negative effects of combined stressors were stronger in populations with low "nutrient history". Additionally, we propose two novel fatty acid (FA) biomarkers, one based on FA unsaturation, 16:3n-3/16:2n-6, and the other on FA elongation processes, 18:2n-6/16:2n-6. Fatty acid analyses showed a significant decrease in 16:3n-3/16:2n-6 and 18:3n-3/18:2n-6 with increases in temperature and nutrients; a more drastic decline was found under the interaction of both stressors. Our results point out that C16 PUFAs, that are synthesized within the "prokaryotic pathway", are more sensitive to thermal and the combined thermal + nutrients stressors than C18 PUFAs, which are synthesized within the "eukaryotic pathway". In general, following a month of control conditions, a clear recovery of most of the seagrass descriptors was observed, highlighting the great capability of Halophila stipulacea to recover from stress conditions. Our results have important ecological and management implications to the seagrass meadows in the GoA and elsewhere. For seagrasses to survive climate change, managers must put efforts into limiting other stressors such as eutrophication that would potentially reduce the seagrass resilience to climate change.